Improved the Activity of Phosphite Dehydrogenase and its Application in Plant Biotechnology - Liu, Tongtong; Yuan, Lili; Deng, Suren; Zhang, Xiangxian; Cai, Hongmei; Ding, Guangda; Xu, Fangsen; Shi, Lei; Wu, Gaobing; Wang, Chuang (Frontiers in Bioengineering and Biotechnology, 2021)
Phosphorus is a nonrenewable resource, which is one of the major challenges for sustainable agriculture. Although phosphite (Phi) can be absorbed by the plant cells through the Pi transporters, it cannot be metabolized by plant and unable to use as P fertilizers for crops. However, transgenic plants that overexpressed phosphite dehydrogenase from bacteria, can utilize phosphite as the sole phosphorus source. In this study, we aimed to improve the catalytic efficiency of phosphite dehydrogenase from Ralstonia sp.4506 (PtxDR4506), by directed evolution. Five mutations were generated by saturation mutagenesis at the 139th site of PtxD R4506 and showed higher catalytic efficiency than native PtxDR4506. The PtxDQ showed the highest catalytic efficiency (5.83-fold as compared to PtxDR4506) contributed by the 41.1% decrease in the Km and 2.5-fold increase in the kcat values. Overexpression of PtxDQ in Arabidopsis and rice showed increased efficiency of phosphite utilization and excellent development when phosphite was used as the primary source of phosphorus. High-efficiency phosphite dehydrogenase transgenic plant is an essential prerequisite for future agricultural production using phosphite as phosphorus fertilizers.